1995
DOI: 10.1007/bf00203659
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of microfibrils and microtubules in developing tension-wood fibres of Japanese ash (Fraxinus mandshurica var. japonica)

Abstract: Abstract. The orientation of cellulose microfibrils (MFs) and the arrangement of cortical microtubules (MTs) in the developing tension-wood fibres of Japanese ash (Fraxinus mandshurica Rupr. var.japonica Maxim.) trees were investigated by electron and immunofluorescence microscopy. The MFs were deposited at an angle of about 45 ~ to the longitudinal axis of the fibre in an S-helical orientation at the initiation of secondary wall thickening. The MFs changed their orientation progressively, with clockwise r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…In plants, FESEMs use so far has been limited to simultaneously viewing CMTs and cell walls in partially extracted onion root tips (Vesk et al, 1994) and tobacco BY-2 cells (Vesk et al, 1996) and determining the alignment of CMFs in some woody species (Abe et al, 1995;Prodhan et al, 1995). To view the innermost layer of primary cell walls, we planed a thin layer from the frozen root surface and gently ex- tracted cytoplasmic material from the exposed cells with sodium hypochlorite.…”
Section: Fesem Observations Of the Walls Of In Situ Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In plants, FESEMs use so far has been limited to simultaneously viewing CMTs and cell walls in partially extracted onion root tips (Vesk et al, 1994) and tobacco BY-2 cells (Vesk et al, 1996) and determining the alignment of CMFs in some woody species (Abe et al, 1995;Prodhan et al, 1995). To view the innermost layer of primary cell walls, we planed a thin layer from the frozen root surface and gently ex- tracted cytoplasmic material from the exposed cells with sodium hypochlorite.…”
Section: Fesem Observations Of the Walls Of In Situ Cellsmentioning
confidence: 99%
“…To view the innermost layer of primary cell walls, we planed a thin layer from the frozen root surface and gently ex- tracted cytoplasmic material from the exposed cells with sodium hypochlorite. Conventional sliding microtomes are often used for cryo-sectioning (Takeda and Shibaoka, 1978;Hogetsu, 1986;Abe et al, 1995;Prodhan et al, 1995) but in this study, a cryoultramicrotome cooled to Ϫ120°C with liquid N 2 was used to prevent structural deformation by ice crystals. Dimethyl sulfoxide (DMSO) was used as a cryoprotectant for the same reason.…”
Section: Fesem Observations Of the Walls Of In Situ Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B, 3B) [33][34][35][36][37][38]. In some species having no G-layer in reaction wood, it has been reported that microfibril angle of S2 layer decreased [15,[39][40][41][42] reported that the microfibril angle of S2 layer was very small (5 to 10 degrees) in reaction wood of Magnolia acuminate and Liriodendron tulipifera.…”
Section: Microfibril Angle In Tension Wood Fibermentioning
confidence: 99%
“…More detailed investigation is still needed to clarify the changes of microfibril angle in the S2 layer for many other species with three-layered secondary wall without G-layer. It is well known that microfibril angle in wood fiber gradually changes from secondary wall to G-layers [34,36,37]. In Fraxinus mandshurica, the microfibril changed its orientation angle progressively, with clockwise rotation, from the S-helix until it was oriented approximately parallel to the fiber axis [37].…”
Section: Microfibril Angle In Tension Wood Fibermentioning
confidence: 99%